2019
DOI: 10.1016/s1470-2045(18)30907-0
|View full text |Cite
|
Sign up to set email alerts
|

Cabozantinib in advanced non-clear-cell renal cell carcinoma: a multicentre, retrospective, cohort study

Abstract: Contributors NMC and LCH were responsible for study design, study coordination, cumulative data collection, data interpretation, and primary manuscript writing. WX did the statistical analyses and participated in the manuscript drafting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 138 publications
(96 citation statements)
references
References 34 publications
6
90
0
Order By: Relevance
“…Data for more recently approved agents in this space is emerging. Although the results for cabozantinib are retrospective, 28,29 the data are promising. In addition, Keynote 427, 30 a phase 2 trial of single‐agent pembrolizumab in treatment‐naïve nccRCC patients, reported an ORR of 25.4% for pRCC (n = 118), adding to a number of retrospective reports with nivolumab in ncRCC 31‐33 .…”
Section: Discussionmentioning
confidence: 99%
“…Data for more recently approved agents in this space is emerging. Although the results for cabozantinib are retrospective, 28,29 the data are promising. In addition, Keynote 427, 30 a phase 2 trial of single‐agent pembrolizumab in treatment‐naïve nccRCC patients, reported an ORR of 25.4% for pRCC (n = 118), adding to a number of retrospective reports with nivolumab in ncRCC 31‐33 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the data cutoff for this analysis was May 15, 2017, more recently approved drugs for mRCC treatment had been documented for only a few (such as for nivolumab) or for none of the patients with pmRCC (such as for cabozantinib). Recent retrospective data suggest that CPI and cabozantinib might be interesting treatment strategies in nccRCC. Further prospective data are warranted, and some clinical trials are ongoing in this field .…”
Section: Discussionmentioning
confidence: 99%
“…With 13 patients included, median OS was 4 months, with a response rate of 23% (1 response with Temsirolimus, 1 with Sorafenib and 1 with Sunitinib). Another recent study published in 2019 (19) tested the efficacy of Cabozantinib in metastatic nonn-clear-cell renal cell carcinoma; amongst the 112 patients included, there were 4 cases of CDC, with a 50% response rate to Cabozantinib.…”
Section: Discussionmentioning
confidence: 99%